2003
DOI: 10.1074/jbc.m212626200
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Rafts Play a Crucial Role in Receptor Activator of Nuclear Factor κB Signaling and Osteoclast Function

Abstract: Membrane lipid rafts play a key role in immune cell activation by recruiting and excluding specific signaling components of immune cell surface receptors upon the receptor engagement. Despite this, the role of these microdomains in the regulation of osteoclasts as controlled by receptor activator of nuclear factor B (RANK) has yet to be established. In this study, we demonstrate that the raft microdomain expression plays an essential role in osteoclast function and differentiation. Expression of raft component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 49 publications
(60 reference statements)
3
70
0
Order By: Relevance
“…Furthermore, raft-disrupting agents destroyed the integrity of actin-ring structure, boneresorbing activity, and survival of osteoclasts. However, raft disruption did not impaired MAPK and NF-κB activation by RANKL (Ha et al, 2003). In this study, we demonstrated that the majority of the overexpressed RANK was localized in lipid rafts portion (Figure 1).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, raft-disrupting agents destroyed the integrity of actin-ring structure, boneresorbing activity, and survival of osteoclasts. However, raft disruption did not impaired MAPK and NF-κB activation by RANKL (Ha et al, 2003). In this study, we demonstrated that the majority of the overexpressed RANK was localized in lipid rafts portion (Figure 1).…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, TRAF6 has been shown to translocate to lipid rafts in osteoclasts upon activation of another TNF-R family member, the receptor activator of nuclear factor kB (RANK). In addition, the TRAF-6 translocation following RANK engagement was accompanied by Akt activation, a phenomenon inhibited by lipid raft disruption [46]. Therefore, in our study, CD40-mediated PI-3K activation might be dependent on lipid rafts translocation due to the type of TRAF upstream of its signaling.…”
mentioning
confidence: 56%
“…Moreover, EEIG1 could associate with Tec/Btk but not Syk. Further, we observed that after RANKL stimulation, EEIG1, Gab2, Btk, as well as RANK, were recruited to membrane lipid rafts ( Figure 6J), which are crucial signaling domains for RANK signal transduction [29,30]. Thus, it is likely that the RANK signaling complex generated upon RANKL stimulation contributes to the RANK-mediated osteoclastogenic signaling.…”
Section: Han Kyoung Choi Et Al 531mentioning
confidence: 75%